Scott & Witty Wikky : A Young Inventor's Quest - Gee, Perry; Sparky Animation (Singapore : WS Education, an imprint of World Scientific Publishing Co. Pte. Ltd., 2016)
Ten-year-old Scott Sun enjoys school much more than his friend Ming Pok, especially when an assignment leads to the possibility of winning a prize for inventing something that will solve a real-life problem. Includes definitions and explanations from Scott's usually invisible friend, Wikky.
Keywords: Self-actualization (Psychology) -- Fiction; Conduct of life -- Fiction